Integration Of CaO/K₂O Heterogeneous Catalysts with Response Surface Methodology for Efficient Biodiesel Production From Waste Cooking Oil - Agung Prabowo; Syarifudin Oko; Muh Irwan; Gading Bagus Mahardika; Heni Sugesti (Jurnal Inovasi Teknik Kimia, 2026)
Waste cooking oil (WCO) is a promising low-cost feedstock for biodiesel production; however, its high impurity content and variable composition often limit conversion efficiency, particularly in single-step heterogeneous catalysis. This study addresses this challenge by developing a CaO/K₂O heterogeneous catalyst derived from waste chicken eggshells and optimizing the transesterification process using Response Surface Methodology (RSM). Unlike previous studies primarily focused on yield enhancement, this work integrates statistical optimization with GC–MS-based analysis to elucidate catalyst-dependent selectivity in fatty acid methyl ester (FAME) distribution. The results show that reaction time is the dominant factor influencing biodiesel yield, while catalyst loading has a comparatively minor effect within the investigated range. Under optimal conditions (4.5 g catalyst, 4.5 h), a biodiesel yield of 69.6% was achieved, which is moderate compared to reported values (>85%) but acceptable considering the use of untreated WCO and a low-cost waste-derived catalyst. Fuel properties generally met international standards, although the acid value slightly exceeded the limit due to residual free fatty acids. This study highlights the trade-off between process simplicity and conversion efficiency and provides new insights into structure–activity–selectivity relationships in CaO/K₂O-based systems, offering a practical pathway for sustainable biodiesel production from low-quality feedstocks.